2021
DOI: 10.1038/s41598-020-80431-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of chloroplast genomes indicated different origin for Indian tea (Camellia assamica cv TV1) as compared to Chinese tea

Abstract: Based upon the morphological characteristics, tea is classified botanically into 2 main types i.e. Assam and China, which are morphologically very distinct. Further, they are so easily pollinated among themselves, that a third category, Cambod type is also described. Although the general consensus of origin of tea is India, Burma and China adjoining area, yet specific origin of China and Assam type tea are not yet clear. Thus, we made an attempt to understand the origin of Indian tea through the comparative an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Bayesian clustering and phylogenetic analyses in these studies (36,37) indicated that the Chinese CSA tea may have been domesticated from C. grandibracteata, and CSS from C. ptilophylla or C. leptophylla. These findings were generally consistent with results of plastomic analyses of species in Camellia/Theaceae (26,(38)(39)(40), further reinforcing the view that C. grandibracteata and C. leptophylla might have been involved in the domestication of tea. Although the above studies did shed some light on the evolutionary origin of tea, controversies still abound; for instance, the phylogeny of Huang et al (36) indicated that CSS and CSA might have undergone independent domestication from two different progenitors, while Rawal et al (40) suggested that CSS may have descended from CSA.…”
Section: Domestication History Of Teasupporting
confidence: 84%
See 3 more Smart Citations
“…Bayesian clustering and phylogenetic analyses in these studies (36,37) indicated that the Chinese CSA tea may have been domesticated from C. grandibracteata, and CSS from C. ptilophylla or C. leptophylla. These findings were generally consistent with results of plastomic analyses of species in Camellia/Theaceae (26,(38)(39)(40), further reinforcing the view that C. grandibracteata and C. leptophylla might have been involved in the domestication of tea. Although the above studies did shed some light on the evolutionary origin of tea, controversies still abound; for instance, the phylogeny of Huang et al (36) indicated that CSS and CSA might have undergone independent domestication from two different progenitors, while Rawal et al (40) suggested that CSS may have descended from CSA.…”
Section: Domestication History Of Teasupporting
confidence: 84%
“…The early speculations by Ward (22) about the origin of CSS and CSA were later partly supported by some empirical genetic/genomic studies (18,25,26), which demonstrated that cultivated CSS and CSA might have different geographical origins. An emerging idea, however, is that CSA in China and India are genetically distinct (though morphologically similar), indicating independent geographic and evolutionary origin for the two CSA groups (18,26).…”
Section: Geographical Origin Of Teamentioning
confidence: 94%
See 2 more Smart Citations
“…According to cluster analysis, various types of intermediate hybrids and spontaneous polyploids are found because tea trees can easily hybridize, and there is likely just a single place/area of origin for Camellia sinensis on earth. This place is believed to be the adjoining area of the Yun Nan and Si Chuan provinces of China, India, and northern Burma [ 35 ].…”
Section: China the Birthplace Of Teamentioning
confidence: 99%